Analisa Dampak Simulasi Bayangan Objek pada PLTS 1,3 MWp Menggunakan Software SAM - Hendra Budiono Putra Parapa' (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
There are several factors that influence the performance of a PLTS, one of which is related to the impact of shadows falling on the surface of the photovoltaic module. The impact of shadows on the performance of PLTS is the driving factor for carrying out this research. This research aims to analyze the impact of shadow simulation on PLTS using SAM software. The PLTS location discussed in this research is the 1.3 MWp PLTS Selayar, South Sulawesi. The data used is PLTS main equipment specification data and solar radiation data sourced from NSRDB-NREL. The data is then processed using SAM (Supervisory Advisor Model) software to simulate three conditions, without shading, self-shading and vegetation shading. Based on the analysis that has been carried out, it is concluded that there is a decrease in PLTS production in self-shading conditions of 28,616 kWh and a performance ratio of 1.03% compared to conditions without shading, whereas when compared with self-shading and vegetation shading conditions, there is a decrease in production of 81,406 kWh and the performance ratio of 2.94%. This condition shows the need to address the causes of shading, especially shading caused by vegetation around the PLTS environment.